Comparison of Submillinewton Thrust Measurements Between a Laser Interferometer and a Load Cell on a Pendulum Balance - Tsifakis, Dimitrios; Charles, Christine; Boswell, Rod (Frontiers in Space Technologies, 2021)
Reliable measurements of thrust from systems to be flown on satellites are essential to ensure repeatable manoeuvring capability of small nano-satellites. Thrusters can be used to vary spacecraft orientation, detumbling and orbit change. Tests have been conducted in a low pressure vacuum system using a cold gas prototype thruster and two independently calibrated methods: a 4 point pendulum with a laser interferometer displacement sensor and a load cell, both of which have measurement capabilities from tens of micronewtons to tens of millinewtons. The agreement is very good lending to confidence in both methods. The advantages and disadvantages of both methods will be discussed: absolute accuracy, low thrust accuracy, temporal resolution, simplicity of operation, cost and sensitivity to vibrations generated by laboratory equipment such as pumps, fans, bumps and human movement.